Noninvasive Prenatal Testing Using Fetal Fraction Enrichment-A Pilot Study - Yun Chen; Yunli Lai; Jian Yi; Shang Yi; Xiaoshan Huang; Yanqing Tang; Jiasun Su; Yiping Shen; Hongwei Wei (IMR Press, 2024)
Background: To evaluate the clinical performance and clinical implementation of noninvasive prenatal testing (NIPT) using fetal fraction (FF) enrichment. Methods: Both standard NIPT and NIPT with FF enrichment were performed concurrently to 277 clinical samples. Results: On average, the FF of each sample processed by NIPT with FF enrichment was 1.9-fold higher than without enrichment. 88% (43/49) of samples with low FF in standard NIPT were recovered by the enrichment method. 11 more copy number variants (CNVs) which were confirmed by prenatal diagnosis were detected by NIPT with FF enrichment. NIPT with FF enrichment generated a positive predictive value of 75% for CNVs (≥3 Mb and 22q11.2 ≥1 Mb). NIPT with FF enrichment showed similar performance in the detection of common trisomy when compared with the standard method. Pregnant women with higher body mass indexes experienced significantly greater enriching effects on FF from NIPT with the enrichment protocol. Conclusions: NIPT with FF enrichment effectively elevated the FF level. This method is capable of detecting significantly more concordant CNVs with a positive predictive value (PPV) of 75%. Our data suggest that this enhanced version of NIPT can be used to improve the screening performance of clinically significant fetal CNVs but it should only be recommended when comprehensive counseling is available.